Creación deproblemas para el estudio del álgebra y composición de funciones utilizando aplicativos - Luna Valenzuela, Maritza (2021)
The objective of this workshop is the creation of problems about algebra and the composition of functions, for which will be created using GeoGebra software. The aim is to motivate the ability to critically evaluate the quality of a mathematicalactivity around the solution of a problem and to have the ability to modify it in order to achieve enriching mathematical activities. To achieve this purpose, the strategy of problem creation by variation will be applied, which consists of presenting the participants with a problem, in the framework of a very concrete episode, in a teacher's class, this episode briefly describes some of the reactions of his students when solving the problem. After a sequence of activities, the participants will create and solve problems, and finally, they will socialize synchronously about their experience in the workshop.